2017
DOI: 10.5194/acp-2017-104
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mean age of stratospheric air derived from AirCore observations

Abstract: <p><strong>Abstract.</strong> Mean age of stratospheric air can be derived from observations of sufficiently long lived trace gases with approximately linear trends in the troposphere. Mean age can serve as a tracer to investigate stratospheric transport and long term changes in the strength of the overturning Brewer-Dobson circulation of the stratosphere. For this purpose, a low-cost method is required in order to allow for regular observations up to altitudes of abou… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Our analysis of the 25‐year NDACC data records from nine stations provides observational evidence that the southern extratropical LS has been getting younger relative to the NH at a mean rate of 1 month/decade since 1994, with most of the change originating in the SH (~0.7 month/decade). Like Engel et al (2017), we find a positive but insignificant trend in the NH AoA. The AoA is determined by the BDC and subtropical mixing, so the decrease in SH AoA could mean either increased mixing or increased (accelerated) circulation, or both.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our analysis of the 25‐year NDACC data records from nine stations provides observational evidence that the southern extratropical LS has been getting younger relative to the NH at a mean rate of 1 month/decade since 1994, with most of the change originating in the SH (~0.7 month/decade). Like Engel et al (2017), we find a positive but insignificant trend in the NH AoA. The AoA is determined by the BDC and subtropical mixing, so the decrease in SH AoA could mean either increased mixing or increased (accelerated) circulation, or both.…”
Section: Discussionsupporting
confidence: 81%
“…AoA trends have been addressed using observations of long‐lived trace gases with a known surface trend (Andrews et al, 2001; Engel et al, 2009 & 2017; Schoeberl et al, 2005; Waugh & Hall, 2002). Engel et al (2017) analyzed 32 CO 2 and SF 6 vertical profiles from 1975 to 2016 and found no significant AoA trend in the northern midlatitude lower and middle stratosphere between 24 and 35 km, but the sparseness of sampling may have precluded any trend detection (Garcia et al, 2011; Waugh, 2009). Analysis of ground‐based and satellite measurements of another long‐lived trace gas, HCl, supported by a model simulation showed that for a short period, 2007 to 2011, dynamical variability caused AoA and HCl to increase in the NH lower stratosphere (LS), while the opposite occurred in the SH (Mahieu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The stratospheric mean age of air is defined as the average transit time for an air parcel to be transported from a reference source region in the troposphere to a specific location in the stratosphere. Several attempts have been made for calculating the age of air in the LS based on trace gas observations (Engel et al., 2017; Hauck et al., 2020; Sawa et al., 2015). In this study, we performed a comparative analysis of monthly mean age of air derived from CO 2 and SF 6 observations and model simulations during 2012–2013 and 2014–2015.…”
Section: Resultsmentioning
confidence: 99%
“…The results show an increase (though not statistically significant) at a rate of 0.24 ± 0.22 years decade −1 (Engel et al 2009). Although this rate has been reduced to 0.15 ± 0.18 years decade −1 by a recent study (Engel et al 2017), these estimates are still apart from the long-term decrease of mean age diagnosed by chemistry-climate models (e.g., Austin et al 2007;Garcia et al 2011). For example, Garcia et al (2011) showed that the AoA trend derived from SF 6 over the period 1965-2006 by the Whole Atmosphere Community Climate Model (WACCM) is −0.086 ± 0.011 years decade −1 .…”
Section: Introductionmentioning
confidence: 85%
“…The importance of this ratio is also evident from a different perspective, which is the long-term trend of the mean age. The slope of 0.15 ± 0.18 years decade −1 (Engel et al 2017) updated from 0.24 ± 0.22 years decade −1 (Engel et al 2009), in the Northern midlatitude stratosphere is further reduced to 0.07 years decade −1 when the model parameters are revised; the value suggested for the ratio of moments is 1.25-2 years (Fritsch et al 2020). Thus, the age estimation based on the measurements of trace gases should be made carefully considering the reality of the parameters assumed in the analysis.…”
Section: Discussionmentioning
confidence: 99%